Case Study : H.A Laksa Laksam Berkuah Beris Pintu Gerbang / Muhammad Khairan Shazuan Jusoff - Jusoff, Muhammad Khairan Shazuan (2020)
The case study project is one of the theories that can be applied to practical situation regarding the technology of business. For the purpose of conducting the case study, I chose Haris Laksa Laksam Berkuah Beris Pintu Geng out of several companies that I had interviewed before. Haris Laksa Laksam is located at Lot 2768, Kampung Pintu Gerbang, 16150 Kota Bharu, Kelantan. In the first part of the case study report, the general information of the company has been collected. In order to get the information about the company, my friends and I have had an interview session with the owner of the company. In the second part of this case study report, it contains the specialized subject study. The objective of the project is to provide information on the background, organizational structure and services that Haris Laksa Laksam provides. Apart from that, I also studied about the technology that is being used in order to produce Laksa and Laksam which are modified steamer and huge pots. This machine is used to produce a high quality Laksa, Laksam and also the sauce (kuah). This part will explain the business, as well as the marketing and operational strategy used by the company to promote its service. Lastly, I also made some research regarding the company’s financial achievements, regarding how they manage their finance and their achievement gained from financial management